Gender Bias in Historiography of Indonesia and the Writing of Women's History - Amini, Mutiah (Yayasan Jurnal Perempuan, 2018)
This paper discusses gender bias within the Indonesian historiography tradition. Various historical literature records that all major events in Indonesian history–as a nation–are masculine and strongly dominated by male narratives. There is no space for women to be present in the narratives of the past. As if the history of Indonesia is a history of men, whereas if critical research is done then women such as men have a past narrative that is also important. Women are present and give meaning to the development of the nation's history. This matter is absent in Indonesian historiography. The strength of gender bias in the historiography of Indonesia can not be separated from the strong patriarchal culture in the life of society. Thus the gender bias ultimately forms a canon, so this is then reproduced from generation to generation. This article argues that critical research by revealing a new fact is a power to change gender bias in Indonesian historiography.